Automated protection Security Assessment of Today's and Future Power Grids - Jäger, Johann; Krebs, Rainer (IEEE Power and Energy Society General Meeting, 2010)
Protection security assessment of power grids becomes an important task in the course of a competitive energy business and a decarbonized power generation. The analysis of past blackouts studied by the North American Electric Reliability Council (NERC) shows that protection relays are involved in about 75% of all major disturbances. One reason for that is the non adequate adaption of the protection systems to the changing network conditions. In particular the relay hidden failures caused relay malfunctions and blackouts, following cascading trippings. This paper presents a new automated method, called SiGuard ®-PSA for assessing the security (selectivity and speed) of protection systems to reduce the risk of unnecessary disturbances and blackouts. It analyzes and assesses the security of protection systems of networks as a whole. Routinely checks of contingency sequences are carried out and reveal bottlenecks of the protection behavior itself and of the coordination of network and protection. The simulation tool PSS®SINCAL is used as engine to provide the possibility of a holistic simulation of network and together with the protection. The handling of the large amount of resulting data is done by an intelligent visualization method like a 'fingerprint' analysis. Economic aspects of unselective protection systems will also be newly introduced and presente